Variability of surface and subsurface phytoplankton blooms in a seasonal coastal upwelling system. (1st September 2022) - Shute, Alex; Kämpf, Jochen; Doubell, Mark; Rodriguez, Ana Redondo; Möller, Luciana; Baring, Ryan; Newman, Michelle
Abstract: Understanding how phytoplankton respond to their physical environment is key to predicting shifts in bloom dynamics under a changing climate. This research investigates phytoplankton dynamics in a seasonal coastal upwelling system of the eastern Great Australian Bight (GAB), South Australia, using >10 years of in-situ mooring and CTD observations together with >18 years of satellite and wind data. Earlier studies concluded that upwelling in the region is driven by interactions between upwelling-favourable winds associated with synoptic weather events during austral summer months (Jan–March) and the formation of a pool of nutrient-rich shelf-bottom water on the Lincoln Shelf, known as the Kangaroo Island (KI) Pool. Surface phytoplankton blooms in the upwelling centre, which form off the southern tip of the Eyre Peninsula, are characterized by chlorophyll-a levels of ∼1–2 mg/m 3 . Our analysis of satellite chl- a data indicates the absence of surface phytoplankton blooms in the upwelling centre in more than a third of all upwelling seasons, despite the existence of statistically similar upwelling-favourable winds. The KI Pool is located ∼100 km upstream from the upwelling centre in a marine region that generally displays very low surface phytoplankton levels. Analysis of water-column data indicates strong interannual variability the KI Pool that is correlated with the intensity of surface phytoplankton blooms in the upwelling centre. The analysis also reveals the existence of substantial (∼1 mg/m 3 chl -a ) subsurface phytoplankton blooms at depths between ∼20 and 70 m in shallower waters of the Lincoln Shelf, where nutrient-rich shelf-bottom water of the KI Pool reaches into the euphotic zone. Our data suggest that subsurface phytoplankton blooms, forming at depths that cannot be detected by satellites, represent a major driver of the upwelling ecosystem of the eastern GAB. Highlights: Explores phytoplankton blooms in a seasonal coastal upwelling system. Discovers significant subsurface phytoplankton blooms. Links surface and subsurface blooms to existence of nutrient-rich shelf-bottom water.